2015
DOI: 10.1287/trsc.2014.0542
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Dynamic Programming for a Class of Long-Horizon Maritime Inventory Routing Problems

Abstract: We study a deterministic maritime inventory routing problem with a long planning horizon. For instances with many ports and many vessels, mixed-integer linear programming (MIP) solvers often require hours to produce good solutions even when the planning horizon is 90 or 120 periods. Building on the recent successes of approximate dynamic programming (ADP) for road-based applications within the transportation community, we develop an ADP procedure to generate good solutions to these problems within minutes. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…One promising method in the field of optimisation and control that has attracted much attention in the recent decades is Approximate Dynamic Programming (ADP) due to its effectiveness in tackling stochastic applications where the state and action spaces are large (Li and Womer, 2015;Medury and Madanat, 2013;Papadaki and Powell, 2002;Papageorgiou et al, 2014;Simão et al, 2009;Van Roy et al, 1997;Zhang and Dietterich, 1995). ADP is a variant of DP which uses approximation in the evaluation of candidate control decisions.…”
Section: Motivations and Objectivesmentioning
confidence: 99%
“…One promising method in the field of optimisation and control that has attracted much attention in the recent decades is Approximate Dynamic Programming (ADP) due to its effectiveness in tackling stochastic applications where the state and action spaces are large (Li and Womer, 2015;Medury and Madanat, 2013;Papadaki and Powell, 2002;Papageorgiou et al, 2014;Simão et al, 2009;Van Roy et al, 1997;Zhang and Dietterich, 1995). ADP is a variant of DP which uses approximation in the evaluation of candidate control decisions.…”
Section: Motivations and Objectivesmentioning
confidence: 99%
“…Travel time is considered as a parameter in both the model, although in practicality voyage time keeps changing depending upon the speed of the vessel. Other researchers such as Agra et al 2013a andPapageorgiou et al 2014a extensively studied ship routing and scheduling problem for a planning horizon and integrated inventory management within the problem for addressing varying supply and demand rates at ports. Each of the respective problem deals with routing of a heterogeneous fleet of ships between multiple ports with limited storage capacity and carrying out loading/unloading operations at ports.…”
Section: Complex Maritime Inventory Routing Modelsmentioning
confidence: 99%
“…In a shipment planning problem of bitumen, Persson and Göthe-Lundgren [23] allow for a vessel to discharge at no more than two ports per voyage. In liquefied natural gas (LNG) transportation, the most common practice is to have full load and full discharge where a vessel travels between only one loading port and discharging port in a trip [4,14,22,25]. In the LNG setting studied by [15], multiple port visits in discharging regions are possible, but the number of ports visits are limited to two due to tank restrictions.…”
Section: A Two-stage Algorithm With Feedbackmentioning
confidence: 99%
“…Although it can be applied to any solution (feasible or infeasible) at any time in the search procedure, we apply it immediately following the construction phase described in Section 3 and to each solution stored in a solution pool of SystemModel-2Port (6). Several authors have shown how local search can be used to find highquality solutions and improve existing solutions [14,19,22,28,29,30]. Note that in [29], one loading region, one discharging region, and voyage-chartered vessels are considered so that a vessel path involves a single inter-regional trip.…”
Section: Mip-based Local Searchmentioning
confidence: 99%